SBS shaping and suppression by arbitrary strain distributions realized by a fiber cioling machine - Engelbrecht, Rainer; Mueller, M.; Schmauß, Bernhard (2009 IEEE / LEOS Winter Topical Meeting, Innsbruck, Austria, 12.-14. Jan., 2009)
Experimental results of coiled fibers with a permanent arbitrary distribution of longitudinal strain along the fiber in order to shape or to suppress significantly the gain spectrum of Stimulated Brillouin Scattering (SBS) are presented.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.sbssha